Assessing the Entrepreneurial University Framework: A Model for Institutional Self-Sufficiency - Dalimunthe, Doli Muhammad Jafar; Harahap, R Hamdani; Dalimunthe, Ritha F; Absah, Yeni (Journal of Ecohumanism, 2024)
This study aims to explore the concept of the Entrepreneurial University at the University of Sumatera Utara, as it seeks to transition into an Independent University, known locally as Perguruan Tinggi Negeri Badan Hukum (PTNBH). A qualitative approach featuring interactive models was employed for the data analysis, drawing on contributions from the academic community and partners as key informants. The findings reveal that USU, in its capacity as a PTNBH, has not yet established specific mindsets or policies to govern entrepreneurial endeavors, resulting in a model that is neither integrated nor cohesive but rather operates in a fragmented manner. Obstacles to the USU’s transformation include inadequate socialization and inconsistent policy implementation. Nonetheless, the USU’s substantial human resource quality and quantity present significant strengths and opportunities for addressing its challenges. This research culminates in the development of an Entrepreneurial University Model designed to unify the academic community’s involvement in all entrepreneurial programmes at the University of Sumatera Utara.